Tanggung Jawab Komisaris Dalam Hal Perseroan Terbatas Mengalami Kerugian - Rosida Diani Diani (Simbur Cahaya, 2018)
The Board of Commissioners is a corporate organ that has the duty to carry out supervision in general and / or specifically in accordance with the articles of association and provide advice to directors. The organ of the commissioner is selected by the General Meeting of Shareholders (GMS) must also be responsible to the GMS. As a supervisor of the performance of the board of directors, what is the responsibility of the commissioner if the company suffers a loss. Legal research used is normative legal research. Normative legal research is legal research that puts law as a system of norms. The norm system in question is regarding principles, norms, rules of law and regulations, court decisions, agreements and doctrines (teachings). In carrying out its duties if the company loses, each member of the board of commissioners is personally responsible for the company's loss if the person concerned is guilty or negligent in carrying out his duties. In the event that the board of commissioners consists of two or more commissioners, the responsibility applies jointly to each member of the board of commissioners. Exceptions to this responsibility are if the member of the commissioner can prove that he has carried out supervision in good faith and prudence for the benefit of a Limited Liability Company (PT) and in accordance with the purpose of the PT, and does not have personal interests, directly or indirectly, for resulting in losses, and has provided advice to directors to prevent the occurrence or continuation of such losses